Pelatihan Sadar Wisata dan Sapta PESONA Bagi Kelompok Pemuda Pokdarwis Eka Harapan Desa Suntenjaya Lembang (Jurnal Sosial & Abdimas, 2022)
The tourism awareness movement is a basic thing that needs to be understood by all people, especially those in the tourist village environment. This movement will encourage the community to be able to play an active role in tourism development in the region. Efforts to increase tourism awareness for the community, especially the youth of Suntenjaya village are very important because this village is currently developing its tourism. Suntenjaya Village has extraordinary beautiful potential, but has not been supported by the readiness of human resources. The preparation of human resources needs to be done through various trainings to improve the quality and capacity of the human resources themselves, so that they can become the main drivers in the development of tourist villages and experience improvements in terms of the economy. This community service is one of the efforts to improve the quality and capacity of human resources in order to increase tourism awareness. The method used is a lecture technique and a participatory approach. The community is directly involved in the training through interactive discussions. From the results of this training, the community has a strong understanding of the importance of developing a tourist village and increasing awareness to be actively involved in the management of a tourist village.